Peran Mosi Integral Yang di Usulkan Muhamad Natsir Pada Tahun 1956 Untuk Keutuhan Negara Kesatuan Republik Indonesia - Zainudin Hasan; Dicko Ade Aryandhana; I Nyoman Octaria Andi Saputra; Yovita Silpiani; Raudatul Zanal Al-Zahra (Universitas Sains dan Teknologi Komputer, 2024)
The Integral Motion proposed by Muhammad Natsir in 1956 played a crucial role in strengthening the integrity of the Unitary State of the Republic of Indonesia (NKRI). This proposal not only aims to strengthen the government's legitimacy, but also becomes a strategic instrument in maintaining political and social stability amidst post-independence political dynamics. By receiving majority support in parliament, the Integral Motion creates a strong foundation for the government to face various internal and external challenges, and accelerate the implementation of urgent policies for national development and national unity. In conclusion, Muhammad Natsir's Integral Motion in 1956 was not only a symbol of political unity, but also confirmed commitment to the integrity of the Republic of Indonesia in facing the dynamic changes of the times.